Energy requirement for the mobilization of vacuolar arginine in Neurospora crassa. - Drainas, C (1982)
The bulk of the intracellular arginine pool in exponentially growing mycelia of Neurospora crassa is sequestered in the vacuoles. Vacuolar arginine effluxes from the vacuoles into the cytosol and is catabolized to ornithine and urea upon nitrogen starvation. The energy requirement for mobilization has been studied by treating nitrogen-starved mycelia with inhibitors or respiration or glycolysis or an uncoupler of respiration. Mobilization was inhibited by the inhibitors or the uncoupler of respiration, but not by the inhibitors of glycolysis. The inhibitors and the uncoupler of respiration reduced the ATP pool and the energy charge of the treated mycelia. The inhibitors of glycolysis reduced the ATP pool but had no effect on the energy charge. The results indicate that mobilization of arginine from the vacuoles requires metabolic energy. The forms of this energy and the mode of its association with the mobilization process are discussed.